2021
DOI: 10.3390/ijms22115759
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Metformin, Folate and Vitamin B12 and the Potential Impact on Fetal Growth and Long-Term Metabolic Health in Diabetic Pregnancies

Abstract: Metformin is the first-line treatment for many people with type 2 diabetes mellitus (T2DM) and gestational diabetes mellitus (GDM) to maintain glycaemic control. Recent evidence suggests metformin can cross the placenta during pregnancy, thereby exposing the fetus to high concentrations of metformin and potentially restricting placental and fetal growth. Offspring exposed to metformin during gestation are at increased risk of being born small for gestational age (SGA) and show signs of ‘catch up’ growth and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 172 publications
0
22
0
Order By: Relevance
“…This could therefore contribute to the observed reduction in fetal growth despite the correction of uterine blood flow by metformin. It has been hypothesised that metformin may also have epigenetic effects on the fetus that could have long-term health consequences via changes in activity of histone modification enzymes or DNA methylation (Bridgeman et al 2018;Owen et al 2021). This highlights the complexity of metformin use in utero and the need for further research in light of the lack of knowledge and understanding of metformin action in fetal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could therefore contribute to the observed reduction in fetal growth despite the correction of uterine blood flow by metformin. It has been hypothesised that metformin may also have epigenetic effects on the fetus that could have long-term health consequences via changes in activity of histone modification enzymes or DNA methylation (Bridgeman et al 2018;Owen et al 2021). This highlights the complexity of metformin use in utero and the need for further research in light of the lack of knowledge and understanding of metformin action in fetal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…2018; Owen et al . 2021). This highlights the complexity of metformin use in utero and the need for further research in light of the lack of knowledge and understanding of metformin action in fetal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, metformin will interfere with the absorption of vitamin B12 and folic acid. Studies have shown that up to 30% of patients taking metformin have B12 deficiency ( 47 , 48 ). In this study, CS showed a good anti-DOP effect, similar to metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Folate and Vitamin B12 participate in the one-carbon metabolism cycle and are essential for the regulation of fetal growth (17). Insufficient levels of folate or vitamin B12 during pregnancy are associated with an increased risk of neural tube defects, poorer cognitive function, spontaneous abortion, stillbirth, fetal growth restriction, preterm delivery, and low birthweight (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an in vivo rodent study elucidated altered dietary ratios of folate and B12 could have more severe effects than individual deficiencies on the expression of transporters, related miRNAs, and DNA methylation in C57BL/6 mice, which play an important role in fetal development ( 44 ). Therefore, an imbalance between folate and vitamin B12 during pregnancy could theoretically cause adverse pregnancy outcomes through placental mechanisms ( 17 ). Our findings provide new insights for further study on the effect of maternal folate and vitamin B12 imbalance on birthweight alteration.…”
Section: Discussionmentioning
confidence: 99%